(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Rosuvastatin (RVT) is a BCS class II antilipidemic crystalline drug, which exhibits low bioavailability due to its very poor aqueous solubility; therefore, it is challenging to develop a proper formulation of RVT. To enhance solubility and bioavailability of this API, an attempt has been made by implementing solid dispersion technique. Solid dispersion (SD) technique is a solubility enhancing technique where one or more active entities are dispersed in an inert medium (matrix or carrier) at solid state. In this study, different ratios of Kollicoat® IR (KIR) and Kollidon® 90F (KF90) polymers were used with API to prepare various formulations by physical mixing (PM) and SD approaches; here solvent evaporation technique was used whereas methanol was used as solvent which was completely evaporated from the homogenously dispersed system by placing in a water-bath at 60-65°C and then in oven for 30 minutes at 50 °C. Among the formulations, RVT-KF90 SD formulations showed the most promising result in in-vitro study in terms of drug release profile (78.04 – 99.21%) in comparison to pure RVT (63.1%) and physical mixing of RVT with those polymers. USP dissolution apparatus type II was used at 37°C ± 0.5°C with 50 rpm to conduct the in-vitro experiment. The experiment also unraveled that the dissolution of RVT improved with increasing the amounts of polymers. Subsequently, stability of the developed formulations was conducted by Fourier transforms infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) as well as scanning electron microscopy (SEM). The results obtained from FTIR ensured no involvement of any significant drug-excipient interaction. Moreover, the DSC study signified thermal stability at high temperature. Besides, the SEM micrograph illustrated homogenous distribution of RVT in the polymer and transformation of crystal-like RVT into amorphous formulations. Dhaka Univ. J. Pharm. Sci. 20(2): 199-211, 2021 (December)